On The Formation Of The IV Turmeobiti In Svaneti Language According To Etseri Sub-dialect - Gurchiani, Ketevan (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
In svanetian dialects like other Kartvelian sub-systems ( of Samegrelo, Lazistan, Lechkhumi, Ratcha, Guria) form the IV group of tense and dialect, which contains the IV turmeobiti. Generally the form of IV turmeobiti of Svaneti dialects is L + ma + the stem of oresent tense + un+ e or L+ma + (stem of oresent tense) e + auxiliary verb. In literary Georgian there is no exactly revelvant verbal form. It coreesponds to the following construction: na - participle with prefix + auxiliary verb: lmgem khui “nashenebvar”. Etseri sub-dialect of balskvemouri dialect reveal the same condition of other Svaneti dialects in terms of forming IV turmeobiti; the follow the general form: with the verbs of both types (transitive, intransitive) lm - prefix is always present, suffixes are more or less different. Also, together with common signs in Etheri speech there are specific facts of phonetic and morphological character.